Evaluation of the Association of Academic Physiatrists Medical Student Summer Clinical Externship. (18th July 2022) - Grewal, Harmandeep; Kim, Soojin; Katz, Nicole B.; Case, Christina M.; Pingenot, Edward; Chung, Yelim K.; Chukwuma, Valentine; Mayer, R. Samuel
Abstract: The Medical Student Summer Clinical Externship is an 8-wk program hosted by the Association of Academic Physiatrists and offered to first year medical students. Various institutions sponsor participants and provide clinical exposure and mentorship opportunities to promote interest in the field. The program has had more than 100 medical student participants. Students were asked to complete a preparticipation and postparticipation survey. Results revealed a statistically significant increase in interest in physiatry and participants' scores for comfort and experience level in obtaining a history of present illness, general physical examination, and managing developmental, musculoskeletal, and neurologic disabilities. The Medical Student Summer Clinical Externship program provides an opportunity for mentorship and exposure to various subspecialties that likely reinforces student interest in those who are predisposed to physiatry. Students' increased comfort level in treating patients with developmental, musculoskeletal, and neurologic disabilities may lead to improvements in the quality of and access to care received by these populations. All participants gain an increased awareness of the scope of practice of physiatry that will hopefully lead to the increased integration of physical medicine and rehabilitation into the care plans and as a standard of care for patients who might greatly benefit.